The PiSpec: A Low-Cost, 3D-Printed Spectrometer for Measuring Volcanic SO2 Emission Rates - Wilkes, Thomas Charles; Pering, Tom David; McGonigle, Andrew John Samuel; Willmott, Jon Raffe; Bryant, Robert; Smalley, Alan Lomas; Mims, Forrest Marion; Parisi, Alfio V.; England, Rebecca Anne (Frontiers in Earth Science, 2019)
The PiSpec is a new, custom-designed, 3D-printed spectrometer based on smartphone sensor technology. This unit has ≈ 1 nm spectral resolution and a spectral range in the ultraviolet of ≈ 280-340 nm, and is specifically configured for the remote sensing of SO2 using Differential Optical Absorption Spectroscopy (DOAS). Here we report on the first field deployment of the PiSpec on a volcano, to demonstrate the proof of concept of the device’s functionality in this application area. The study was performed on Masaya Volcano, Nicaragua, which is one of the largest emitters of SO2 on the planet, during a period of elevated activity, where a lava lake was present in the crater. Both scans and traverses were performed, with resulting emission rates ranging from 3.2 - 45.6 kg s-1 across two measurement days; these values are commensurate with those reported elsewhere in the literature during this activity phase (Aiuppa et al., 2018; Stix et al., 2018). Furthermore, we tested the PiSpec’s thermal stability, finding a wavelength shift of 0.046 nm/˚C between 2.5 - 45 ˚C, which is very similar to that of some commercial spectrometers. Given the low build cost of these units (≈ 500 USD for a one-off build, with prospects for further price reduction with volume manufacture), we suggest these units hold considerable potential for volcano monitoring operations in resource limited environments.